MARKETING STRATEGIES USED BY LIBRARIANS IN A STATE UNIVERSITY LIBRARIES - OSINULU, Lolade F; ADEKUNMISI, Sowemimo R (University of Dar es Salaam Library Journal, 2019)
Academic libraries are currently experiencing changes in the new information age, due to rapidly changing media technologies, increasing users ' preferences and expectations, competition from other information providers such as internet and dwindling library budgets. These necessitate library and information science professionals leverage on competitive marketing approaches to strategically reorient themselves and libraries as information superhighways that individuals cannot do without. This study therefore investigated marketing strategies employed by librarians in a state university library in Nigeria. The study adopted survey research design of ex-post facto type. A validated questionnaire with Cronbach alpha reliability coefficient of 0.69 was used to gather information from all the librarians. The results revealed that user survey studies, books, interlibrary loan services and improved burrowing privileges were prevalent marketing strategies used by librarians. Unstable Internet connectivity and inadequate funding were identified as major challenges to effective marketing of library products and services. The study recommended use of ICT and social media tools; teaching of innovative marketing concepts and principles in Nigerian Library schools and aggressiveness on the part of librarians.